Thyroidectomy using a single-port cervico-mental angle approach - Hua-Shui Li; Qiang Lin; Wen-Jun Xie (Journal of Minimal Access Surgery, 2022)
Background: Over the last two decades, several endoscopic thyroidectomy methods have been developed. However, there are some limitations in these procedures. To date, the optimal surgical approach for thyroid cancer has not yet been developed. This study reported the surgical operation steps, clinical outcomes, and experience of 30 patients who underwent trans-cervico-mental angle single-port endoscopic thyroidectomy (TCMASPET) at our centre. Patients and Methods: A total of 30 patients were enrolled in the present study. Patients underwent unilateral or bilateral thyroidectomy through a cervico-mental angle incision of 2.48 ± 0.31 cm, after which the lymphoid adipose tissues in the central region were dissected. Results: All surgeries were successfully completed. Two patients underwent bilateral thyroid carcinoma resection with bilateral central region lymph node dissection, 23 patients received unilateral thyroid cancer resection with unilateral central region lymph node dissection, four patients underwent unilateral thyroid resection, and one patient received bilateral thyroid resection with unilateral central region lymph node dissection. No permanent post-operative complications were observed. Conclusions: TCMASPET was a safe and feasible approach that was relatively easy to perform. This approach may expand the indications for endoscopic thyroidectomy while maintaining excellent cosmetic outcomes.